IMPLEMENTASI PEMBELAJARAN ANDRAGOGI DALAM PROGRAM PAKET C BAGI WARGA BINAAN DI LAPAS PEREMPUAN KELAS IIB KOTA BENGKULU - Kurniati, Yolanda; Sofino, Sofino; Hutauruk, Lenni Mantili (Comm-Edu (Community Education Journal), 2025)
This study aims to evaluate the implementation of andragogie-based learning in the Package C equality education program implemented at the Class IIB Women's Correctional Institution (Lapas) in Bengkulu City. The main focus of this study is on the pre-implementation stage, the application of andragogy principles, and the learning model applied to the inmates. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study showed that the implementation of andragogy learning in prisons reflected the active involvement of the inmates as learning participants, adjustment of materials to their needs, and the use of experiential learning models. This implementation makes a significant contribution to building independence, confidence, and readiness for social reintegration for female assisted residents.